ANALISIS PROSES PENYEMBELIHAN AYAM BERDASARKAN HALAL ASSURANCE SYSTEM (HAS) 23103 (STUDI KASUS RUMAH POTONG AYAM D’JABUNG PONOROGO): Analysis Of Chicken Slapping Process Based On Halal Assurance System (HAS) 23103 (A Case Study Of Chicken House (RPA) In Jabung Ponorogo) - Devi Urianty Miftahul Rohmah; Arief Rahmawan; Yusuf Wahyu Saputra (Universitas Darussalam Gontor, 2022)
RPA D’Jabung Ponorogo is one of the slaughterhouse that sells poultry slaughtering service and also sells the main ingredient of chicken meat. The importance of halal certification that can be obtained will make RPA D’Jabung continue and still pay attention to the halal policy and can carry out the commitments that have been established. The method used in analyzing food halal in this business is the Halal Assurance System (HAS) 23103 about slaughterhouse. This research aims to assess the results of the slaughtering chicken RPA D’Jabung Ponorogo. The date obtained is analyzed descriptively. The results of the study were seen that the slaughtering of chicken in RPA D’Jabung had adopted the slaughtering process according to Islamic law. In the future RPA D’Jabung can register its business in order to be certified halal and become the only RPA that has been standardized and certified by LPPOM MUI in Ponorogo Regency. In its running effort, RPA D’Jabung under the leadership of Mr. Herman Subyan had his own policy in management and remained steadfast in the halal principle. The observations made at RPA D’Jabung Ponorogo showed that the implementation of the halal assurance system was relatively good. It is evidenced by the application of the process in accordance with HAS 23103. Observation of the 11 aspects of the halal in the manual of SJH slaughterhouse chicken HAS 23103 which meets 11 aspects, among others: (1) halal policy, and (2) materials.